Management control systems - Merchant, Kenneth A. (FT Prentice Hall, 2003)
The book presents an all-encompassing framework within which to consider management control issues. It also presents the needed technical subject content and summaries of the relevant research literature. But perhaps most importantly, it helps students developing their skills of applying the material to specific decision-making situations. This is done with real world text examples and an extensive set of case studies, which reflect the complexity that managers face when using MCSs